1986
DOI: 10.2307/3676859
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Bird Community in Southern Finland

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Ornis Scandinavica. Stability of a bird community in southern FinlandTap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 23 publications
3
42
0
1
Order By: Relevance
“…Earlier findings have suggested that avoidance of the eagle owl might affect the spatial structure of the assemblage of the species studied [16]. The northern goshawk did not display such an effect.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Earlier findings have suggested that avoidance of the eagle owl might affect the spatial structure of the assemblage of the species studied [16]. The northern goshawk did not display such an effect.…”
Section: Introductionmentioning
confidence: 69%
“…In addition to the considerable overlap in their diets [28,29], these three species occupy a wide range of similar habitats, although their preferences differ to some degree. Eagle owls occupy various kinds of semiopen habitats in the study area, while northern goshawks prefer old spruce forests and tawny owls opt for rich deciduous and mixed forests, preferably near eutrophic waters [16]. The birds' preferred territories are obviously their traditional ones, but the preference order of locations is not as obvious.…”
Section: The Guild Of Birds Of Prey Of the Study Areamentioning
confidence: 95%
See 3 more Smart Citations